2010
DOI: 10.1111/j.1365-2265.2009.03729.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thyroid function during gestation is related to breech presentation at term

Abstract: Women with TSH levels above 2.5 mIU/l during end gestation are at risk for breech presentation, and as such for obstetric complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 26 publications
0
31
1
1
Order By: Relevance
“…Our cohorts were identified prospectively during routine clinical practice resulting in a large number of breech presentations all of whom were able to be included in the final analysis irrespective of presentation at the time of delivery; women with breech presentation who had successful ECV were excluded in the previous study. 1 There were no differences in any of the baseline demographics of both groups in our study unlike the previous study where there were a significantly higher number of primiparous mothers in the breech group. 2 While having a similar rate of successful ECV to the previous study 3 (55 vs 54%), we were unable to confirm their findings of higher TSH concentrations increasing the risk of ECV failure; however, they did have a significantly higher number of primiparous mothers in their cohort than our study (66% vs 44%, P < 0Á001) which may have impacted on their results.…”
Section: Variables In Pregnancycontrasting
confidence: 82%
See 3 more Smart Citations
“…Our cohorts were identified prospectively during routine clinical practice resulting in a large number of breech presentations all of whom were able to be included in the final analysis irrespective of presentation at the time of delivery; women with breech presentation who had successful ECV were excluded in the previous study. 1 There were no differences in any of the baseline demographics of both groups in our study unlike the previous study where there were a significantly higher number of primiparous mothers in the breech group. 2 While having a similar rate of successful ECV to the previous study 3 (55 vs 54%), we were unable to confirm their findings of higher TSH concentrations increasing the risk of ECV failure; however, they did have a significantly higher number of primiparous mothers in their cohort than our study (66% vs 44%, P < 0Á001) which may have impacted on their results.…”
Section: Variables In Pregnancycontrasting
confidence: 82%
“…A study from the Netherlands has suggested that maternal thyroid hormone deficiency during late pregnancy is also a risk factor. 1 In this cohort study of 1058 pregnant women, 58 women with breech presentation had higher serum TSH at 36 weeks' gestation than those with cephalic presentation, and TSH level ≥2Á5 mIU/l at 36 weeks' gestation was associated with over a twofold higher risk of breech presentation. They postulated that maternal hypothyroidism (with high TSH) could increase the risk of abnormal foetal position either due to a direct effect of TSH on uterine contractions or due to impaired foetal motor activity resulting from thyroid hormone deficiency.…”
Section: Maternal Thyroid Function In Pregnant Women With a Breech Prmentioning
confidence: 98%
See 2 more Smart Citations
“…In five patients 29,33,38,40,44 a cesarean section was required because of breech presentation, which has previously been corre lated with maternal hypothyroxinemia and hypothyroidism. 56,57 In two women, cesarean sections were performed because of fetal distress, 31,37 in one of whom this distress was probably attributable to the intra-amniotic levo thyroxine injection that was given within 24 h of the mother going into preterm labor.…”
Section: Fetal Thyroid Statusmentioning
confidence: 99%